STRATEGI KOMUNIKASI PEMASARAN PENGINAPAN DI PULAU SIMEULUE DALAM MENARIK MINAT WISATAWAN MANCANEGARA - Lukluk Chasanah (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the marketing communication strategies implemented by local accommodation managers in Matanurung Village, Teupah Tengah District, Simeulue Regency, in attracting foreign tourists. Matanurung Village is a developing marine tourism destination with surfing as its main attraction, despite being located in a remote and isolated area that still faces limitations in infrastructure and formal promotion access. This condition requires lodging managers to develop adaptive and contextual marketing communication strategies. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through field observations, semi-structured interviews, and documentation. The research informants consisted of two accommodation owners and five foreign tourists who had stayed in Matanurung Village. Data analysis used the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing. The results show that the marketing communication strategy of lodgings relies on the use of digital media as a means of initial promotion, which is then reinforced through interpersonal communication and word of mouth. Honesty of information, responsiveness of communication, family-based service, and an authentic stay experience are the main factors in building the trust of foreign tourists. These findings confirm that the integration of digital media and ethical, experience-oriented personal communication is an effective marketing communication strategy for small-scale lodgings in remote areas.